1986
DOI: 10.2340/0001555566404408
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of serum IgE levels in atopic dermatitis

M. Uehara

Abstract: To determine whether serum IgE levels in patients with atopic dermatitis (AD) have a relationship to familial background of atopic respiratory disease (ARD), serum IgE levels were measured in 50 AD patients who had personal history of ARD, 37 AD patients who did not have personal history of ARD but had family history of ARD, and 52 "pure" AD patients who had neither personal nor family history of ARD. The "pure" AD patients showed significantly lower serum IgE levels than AD patients who had personal or family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Increased total serum IgE levels are a hallmark of AD, and it is well known that IL‐4 (a Th2‐type cytokine) induces the class switching to IgM secreting B cells to IgE secreting B cells. Furthermore, elevated serum IgE levels have several effects on skin inflammation [39–41]. IgE expression is known to cause both acute and chronic phase skin symptoms, and it has been reported that repeated painting with DNFB increases serum IgE in NC/Nga mice [5, 7, 9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Increased total serum IgE levels are a hallmark of AD, and it is well known that IL‐4 (a Th2‐type cytokine) induces the class switching to IgM secreting B cells to IgE secreting B cells. Furthermore, elevated serum IgE levels have several effects on skin inflammation [39–41]. IgE expression is known to cause both acute and chronic phase skin symptoms, and it has been reported that repeated painting with DNFB increases serum IgE in NC/Nga mice [5, 7, 9, 10].…”
Section: Discussionmentioning
confidence: 99%